An analysis of free-choice electives in an undergraduate medical degree - Catriona Daly; Jason Last (BMC Medical Education, 2017)
Abstract Background The University College Dublin Elective Programme was introduced in 2005 with the intention of broadening the learning of its undergraduate students. Undergraduate medical students undertake seven free-choice electives during their six-year degree programme. They are permitted to choose electives from any school in the University. Students also have the option of selecting ‘In-Programme’ electives, which are aligned to medical themes. The purpose of this study is to analyse the electives taken by medical students with a view to better understanding the factors that influence their choices. Methods In this mixed methodology study, the quantitative phase consisted of a retrospective analysis of 3318 elective choices associated with 474 medical students between 2006 and 2013. Elective choices were analysed in terms of popularity, difficulty level and subject matter. The prospective qualitative phase consisted of a series of semi-structured focus groups held with current medical students. Discussions from the focus groups underwent thematic analysis with a few to exploring and clarifying the quantitative findings. Results The most frequently chosen electives were In-Programme (38.6%) and Applied Language (21.6%) electives, with patterns not significantly varying from year to year. Male and female students tended to take the same type of electives. Focus group discussions revealed that the primary factor motivating choice was workload, with students preferring less demanding electives. Participants indicated that elective grading and assessment criteria had a significant impact on their choices. Participants described ways in which the elective selection process could be improved, including a desire for more structured electives and a revision of the elective selection process. Conclusions The retrospective data analysis revealed a high level of consistency in medical students’ elective choices from stage to stage and between different year cohorts. Qualitative investigation revealed that medical students tend to focus on grading, assessment strategies and skills development when choosing their electives. The implication that students may be reluctant to take more challenging electives despite having an interest in the subject is one that warrants consideration when designing or adapting programmes for the future. Although these findings are associated with a free-choice elective programme, similar strategies are likely to be employed for the more traditional option-based programmes that are associated with the majority of medical degrees internationally.